Different Sources of Social Support and Their Associations with Academic Engagement and Life Satisfaction Among Nursing and Physiotherapy Students - Maja Kućar; Andreja Brajša-Žganec; Marijana Neuberg (Psychology International)
Background: The role of social support in fostering academic engagement (AE) and life satisfaction (LS) is well established, as both are essential for student well-being and success. Theoretical frameworks suggest that distinct sources of social support contribute uniquely to these outcomes. However, limited research has explored these relationships in specific populations, such as nursing and physiotherapy students. Methods: This study aimed to examine the differential relationships between three sources of social support (family, significant other, and friends), AE and LS in a sample of 363 university students (84% female, Mage = 26.52, SD = 8.13) in Croatia (nursing and physiotherapy program). A cross-sectional design was employed using self-reported data. Results: The results of a hierarchical regression analysis revealed that family support was the only significant positive predictor of both AE and LS. Among the demographic variables, an older age was associated with higher AE and LS, while employed students reported lower LS. The findings were consistent across younger (18–24 years) and older (25–48 years) subgroups, with the exception of older students’ AE, where none of the social support sources emerged as significant predictors. Regarding bivariate correlations, all three social support subscales correlated positively with AE and LS, but the correlations were higher for LS. Conclusions: These results highlight the central role of family support in academic and life outcomes for nursing and physiotherapy students, offering insights for targeted interventions to enhance student well-being.